Eco-innovation in the chemical manufacturing industry: Status and its determinants / Keshminder Singh Jit Singh - Keshminder Singh, Jit Singh (2017)
Eco-innovation has emerged as an imperative technological paradigm for governments and firms seeking to promote sustainable manufacturing practices propelling towards the green growth path. This study aims to identify the state of eco-innovation of the chemical industries. The study further develops a holistic eco-innovation framework and empirically examines the determinants of eco-innovation in the Malaysian chemical-manufacturing firms. A sequential exploratory design was used for the purpose of this study. The qualitative analysis deploys a case study approach where semi-structured interviews with six chemical firms were conducted to gauge the state of eco-innovation practices and to validate the holistic eco-innovation framework, based especially on the nine eco-innovation drivers identified from the literature. Survey questionnaires were then distributed to the chemical firms located in the state of Selangor and the data was used to empirically examine the relationship between the eco-innovation drivers and eco-innovation. For this purpose, the Partial Least Square (PLS) technique was used. The results show that in terms of state of eco-innovation, firms are largely net adopters. However, the level of creation of eco-innovation taking place indicated that firms have embraced advanced sustainable manufacturing practices and concepts. Firms are moving away from eco-innovations that merely treat pollutants at the end of manufacturing process to eco-innovations that manage these pollutants at the initial stage of production. Credit for the success of eco-innovation and sustainable manufacturing practices that firms have achieved thus far is due to high top management commitment and strong corporate environmentalism culture. Meanwhile, the eco-innovations framework structured based on the interviews, exhibited a merger of three sub-models, namely; resources, strategy and eco-innovation models that link the eco-innovation drivers through direct and indirect linkages. Eco-innovation in the chemical firms was mainly driven by the firms’ environmental strategies and environmental regulations. Environmental strategies display a central tendency to connect with other eco-innovation drivers within the eco-innovation framework. Export behaviour and environmental collaboration, meanwhile exhibited strong indirect effect on eco-innovation through environmental strategies. The implications of the study are as follows. Although governmental actions through command and control policies have in the past promoted eco-innovation among firms, however, it was increasing demand for green products and emerging environmental issues that thrusted firms into their environmental strategies entailing for more flexible policy options such as informational measures, voluntary agreements and credible price signal. Firms also had an urgent need to strengthen their absorptive capacity due to huge amounts of practical and tacit knowledge involved during environmental strategy formulation but with no proper mechanism in place to capture this knowledge. On the theoretical front, the study confirms that the mix of theories and knowledge from the field of environmental economics, innovation economics and management are imperative to effectively develop a holistic eco-innovation framework and to provide practical solutions to problems related to eco-innovation. The study and its findings are still largely exploratory and sector specific, which limits generalization of the results. Therefore, a similar study in other manufacturing sectors is required to validate the eco-innovation framework and results.